Lessons from the Portuguese Political-Economic Transition to the Euro (1986-1999) - Sousa, Miguel Rocha de (2013)
We show the Portuguese transition to the euro, in the framework of political economics, by constructing a bivariate confidence index, based upon Rocha de Sousa (1998, 1999a,b, 2001). Besides we try to understand if the euro functioned as an instrument of politico-economic integration. The article has the following structure: section 1 shows the process of monetary European construction, section two illustrates the need for budget consolidation before the euro, section three illustrates the notion of monetary credibility and the construction of a bivariate politico-economic index, section four illustrates the role of ECB and of the SECB, section 5 assesses the study of euro impact on Portugal and, section 6 evaluates EMU after 10 years based upon EC (2008) and, finnally, section 7 concludes.